Pathway Analysis of Patients with Severe Acute Respiratory Syndrome - Khaleel, Anas; Zakariya, Abdullah Bassam; Niazi, Mohammad; Qinna, Nidal A.; Dayyih, Wael Abu; Tarkhan, Amneh H. (Drug research (Stuttgart), 2022)
Abstract Background Coronaviruses are emerging threats for human health, as demonstrated by the ongoing coronavirus disease 2019 (COVID-19) pandemic that is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is closely related to SARS-CoV-1, which was the cause of the 2002–2004 SARS outbreak, but SARS-CoV-1 has been the subject of a relatively limited number of studies. Understanding the potential pathways and molecular targets of SARS-CoV-1 will contribute to current drug repurposing strategies by helping to predict potential drug-disease associations. Methods A microarray dataset, GSE1739, of 10 SARS patients and 4 healthy controls was downloaded from NCBI’s GEO repository, and differential expression was identified using NCBI’s GEO2R software. Pathway and enrichment analysis of the differentially expressed genes was carried out using Ingenuity Pathway Analysis and Gene Set Enrichment Analysis, respectively. Results Our findings show that the drugs dexamethasone, filgrastim, interferon alfacon-1, and levodopa were among the most significant upstream regulators of differential gene expression in SARS patients, while neutrophil degranulation was the most significantly enriched pathway. Conclusion An enhanced understanding of the pathways and molecular targets of SARS-CoV-1 in humans will contribute to current and future drug repurposing strategies, which are an essential tool to combat rapidly emerging health threats.